2018
DOI: 10.1108/cdi-09-2017-0171
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions of education and employability

Abstract: Purpose -The purpose of this paper is to understand how students perceive their future careers and how university has prepared them to enter the global labor market; student perceptions regarding benefits vs associated costs of pursuing higher education (HE) on employability and earnings; and the anticipated barriers and how to overcome these in pursuit of career sustainability within a career ecosystem. Design/methodology/approach -The authors adopted a qualitative method using semi-structured interviews on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(137 citation statements)
references
References 74 publications
7
86
0
Order By: Relevance
“…The overall perception of the employers from the present study confirm that all of the stakeholders may benefit from these results for acontinuous assessment of graduates and undergraduates skills to build strategies for attracting and retaining graduates [58] for a well-qualified labour force.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The overall perception of the employers from the present study confirm that all of the stakeholders may benefit from these results for acontinuous assessment of graduates and undergraduates skills to build strategies for attracting and retaining graduates [58] for a well-qualified labour force.…”
Section: Discussionsupporting
confidence: 62%
“…Lack of employability skills is one of the problems employers face with graduates or their future employees [58]. Candidates may have the qualifications and hard skills needed to be able to manage the job but, without a well-honed set of soft skills, employers are less inclined to hire.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that universities are associated with increased employability (Donald, Ashleigh, & Baruch, 2018). However, embedding employability in the core of higher education is still an open issue (Sin & Amaral, 2017).…”
Section: Responsibilit Y Of the Univer Sit Y In Employabilit Ymentioning
confidence: 99%
“…Therefore, the authors constructed a career advised model to show the complexity and interrelations between stakeholders. Furthermore, the authors found out that it is important for the government to work together with organizations in order to address the market requirements and create new jobs (Donald, Ashleigh, & Baruch, 2018).…”
Section: Triple Helix and Quadruple Helix Relationshipsmentioning
confidence: 99%